A "spiral" motif: sport, jeu, travail (Signifiances (Signifying), 2021)
This case study shows the presence of a same morpheme [spr] in the French terms spirale, aspirer (to aspire / to suck), inspirer (to inspire), espérer (to hope) and sport. This morpheme is linked to a semantic “motif”, a schematic “spiral” form, whose formulation is consistent with the mathematical definition of spiral curves. This motif contributes to setting the word sport within the lexicon, via morphology on the one hand, and via the lexical triangle formed by sport-jeu-travail (sport-game-work) on the other, as demonstrated by the respective analyses of jeu and travail. It is thus empirically confirmed that sport is both jeu (game) and travail (work). Besides, these descriptions validate the theoretical phenomenological framework in which all language activity is conceived as a perception, and all perception is conceived as semiotic.